Quality traits drive the enrichment of Massilia in the rhizosphere to improve soybean oil content - Qin Han; Guanghui Zhu; Hongmei Qiu; Mingbo Li; Jiaming Zhang; Xinying Wu; Renhao Xiao; Yan Zhang; Wei Yang; Bing Tian; Lanxi Xu; Jiayang Zhou; et al. (Microbiome)
Abstract Background Soybean seeds are rich in protein and oil. The selection of varieties that produce high-quality seeds has been one of the priorities of soybean breeding programs. However, the influence of improved seed quality on the rhizosphere microbiota and whether the microbiota is involved in determining seed quality are still unclear. Here, we analyzed the structures of the rhizospheric bacterial communities of 100 soybean varieties, including 53 landraces and 47 modern cultivars, and evaluated the interactions between seed quality traits and rhizospheric bacteria. Results We found that rhizospheric bacterial structures differed between landraces and cultivars and that this difference was directly related to their oil content. Seven bacterial families (Sphingomonadaceae, Gemmatimonadaceae, Nocardioidaceae, Xanthobacteraceae, Chitinophagaceae, Oxalobacteraceae, and Streptomycetaceae) were obviously enriched in the rhizospheres of the high-oil cultivars. Among them, Oxalobacteraceae (Massilia) was assembled specifically by the root exudates of high-oil cultivars and was associated with the phenolic acids and flavonoids in plant phenylpropanoid biosynthetic pathways. Furthermore, we showed that Massilia affected auxin signaling or interfered with active oxygen-related metabolism. In addition, Massilia activated glycolysis pathway, thereby promoting seed oil accumulation. Conclusions These results provide a solid theoretical basis for the breeding of revolutionary soybean cultivars with desired seed quality and optimal microbiomes and the development of new cultivation strategies for increasing the oil content of seeds. Video Abstract